Utilization of Rice Husk Ash and Fly Ash as Cement Substitutes in Highstrength Concrete - Arif Amrullah; Firdaus Firdaus (Journal of Social Research, 2026)
This study analyzes the effect of rice husk ash (ASP) and fly ash (FA) as partial cement substitutions on the mechanical properties of high-strength concrete. The concrete mix was designed with a target compressive strength of 60 MPa using the SNI 03-6468-2000 method. Substitution variations of ASP and FA were applied at 0%, 5%, 10%, 15%, and 20% of the cement weight. The experimental testing included measurements of unit weight, compressive strength at 7, 28, and 56 days, and modulus of elasticity at 28 days. The results indicate that FA significantly improves concrete unit weight and compressive strength, with optimal performance observed at the 10% substitution level; beyond this percentage, strength tends to stabilize or decrease. Meanwhile, ASP generally reduces concrete unit weight due to its lower specific gravity but still contributes to strength enhancement at certain substitution levels through its pozzolanic reaction, which strengthens the concrete microstructure over time. Both FA and ASP demonstrate substantial potential in improving the performance characteristics of high-strength concrete, particularly in terms of compressive strength and durability. Additionally, their utilization supports sustainable construction practices by reducing cement consumption and mitigating the environmental impact associated with industrial and agricultural waste disposal, making them viable eco-friendly supplementary cementing materials.